Motor self-efficacy and physical education in school bullying - Galán-Arroyo, Carmen; Flores-Ferro, Elizabeth; Castillo-Retamal, Franklin; Rojo-Ramos, Jorge (Frontiers in Psychology, 2024)
In recent years, there has been a notable increase in bullying rates in school. Bullying is characterized as a repeated set of malicious actions by an individual or group towards another individual in an imbalanced power dynamic, resulting in physical, psychological, social, or material harm to the victim, with the intention of causing social exclusion. The scientific literature has investigated the factors that influence this type of behavior, environmental factors, such as school location and student age, as well as other factors, such as gender and level of physical fitness, also play an important role. This study examined the correlation between motor self-efficacy and bullying, considering that physical activity acts as a regulator in these cases. The Kolmogorov-Smirnov test was employed to assess the normality of the data distribution, and Spearman's Rho test was used to analyze the relationship between each dimension of the EBIPQ and E-AEM scores. The Cronbach's alpha was used to evaluate the reliability of each instrument.The results indicated a significant inverse correlation between the EBIP-Q and E-AEM in the variables of sex, educational stage and school environment. In conclusion, an inverse correlation was observed between motor self-efficacy and bullying, indicating that higher levels of motor self-efficacy are related to lower levels of bullying victimization. Motor self-efficacy could be used as a tool to reduce bullying situations at school. It would be important for government policies to encourage the practice of physical activity in all areas of life in order to improve motor self-efficacy and end bullying.